Emergencial Remote Education: study case of the subject “Process Control and Instrumentation” of the Chemical Engineering course from UTFPR, Ponta Grossa campus (Research, Society and Development, 2021)
Historically, attendance is a very characteristic factor of engineering courses, but recently due to the adversities of the Covid-19 pandemic, it was necessary to implement emergency remote teaching systems to qualify professional engineers, in order not to lose the quality of teaching and supplying the need for professionals demanded by the new industry 4.0 revolution, disruptive and innovative actions were worked to overcome this moment. In this sense, this paper aims to understand how students' academic performance was during the period of emergency remote teaching in the discipline of Process Control and Instrumentation, in addition to discussing nuances of the methodology incorporated for the subject in question in this teaching model. The case study was done with the discipline of Process Control and Instrumentation, from the 7th period of Chemical Engineering at UTFPR, campus of Ponta Grossa.